In the night of memory : a novel - Grover, Linda LeGarde (University of Minnesota Press, 2019)
Two lost sisters find family, and themselves, among the voices of an Ojibwe reservation. When Loretta surrenders her young girls to the county and then disappears, she becomes one more missing Native woman in Indian Country's long devastating history of loss. But she is also a daughter of the Mozhay Point Reservation in northern Minnesota and the mother of Azure and Rain, ages 3 and 4, and her absence haunts all the lives she has touched--and all the stories they tell in this novel. In the Night of Memory returns to the fictional reservation of Linda LeGarde Grover's previous award-winning books, introducing readers to a new generation of the Gallette family as Azure and Rain make their way home. After a string of foster placements, from cold to kind to cruel, the girls find their way back to their extended Mozhay family, and a new set of challenges, and stories, unfolds. Deftly, Grover conjures a chorus of women's voices (sensible, sensitive Azure's first among them) to fill in the sorrows and joys, the loves and the losses that have brought the girls and their people to this moment. Though reconciliation is possible, some ruptures simply cannot be repaired; they can only be lived through, or lived with. In the Night of Memory creates a nuanced, moving, often humorous picture of two Ojibwe girls becoming women in light of this lesson learned in the long, sharply etched shadow of Native American history.